Effect of modified coal tar pitch addition on the microstructure and properties of Al2O3–SiC–C castables for solid waste incinerators. Issue 14 (15th July 2022) - Wang, Shijie; Zhou, Pingyi; Liu, Xin; Cui, Junyan; Liu, Xinhong; Zhang, Shaowei; Jia, Quanli
Abstract: Al2 O3 –SiC–C (ASC) castables were performed using brown alumina, SiC, ultrafine α-Al2 O3, microsilica, Si powder, calcium aluminate cement and modified coal tar pitch (CP) as starting materials. Effect of CP content and firing atmosphere on the microstructure and properties of ASC castables were investigated. The results show that cold strength, hot strength, thermal shock resistance and slag resistance of ASC castables were slightly improved with increasing of CP content. As an example of castables containing 2 wt% CP, it can be found that the cold strength and hot strength of the sample after firing in oxidizing atmosphere and reducing atmosphere were higher than that of in weak oxidizing atmosphere, and the sample after firing in reducing atmosphere possess overall properties including higher strength, good thermal shock resistance and slag resistance. The differences in properties of ASC castables with different CP addition were closely related to their phase compositions, microstructure including pore size distribution, and the amount of in-situ formed SiC whiskers.